A taxonomic revision of the weevil genus Picia Tournier, 1895 (Coleoptera: Curculionoidea: Erirhinidae) - Caldara, Roberto (Zootaxa, 2008)
The Palaearctic weevil genus Picia Tournier, 1895 is revised for the first time. Three valid species are recognised: P. sinuatocollis (Faust, 1885), P. mesopotamica (Tournier, 1889) and P. syriaca (Reitter, 1889). The following new synonymies are proposed: P. sinuatocollis (= Faustia ephimeropoides Tournier, 1889 syn. n.; = Ephimeropus fenestratus Reitter, 1889 syn. n.; = Picia alfierii Pic, 1914 syn. n.; = Picia druinei Pic, 1917 syn. n.; = Hydronomidius punjabensis Pajni & Kamal Tewari, 1985 syn. n.); P. mesopotamica (= Faustia caucasica Tournier, 1889 syn. n.; = Faustia millingi Tournier, 1889 syn. n.; = Ephimeropus flaveolus Reitter, 1889 syn. n.; = Picia distinctipennis Pic, 1901 syn. n.). Faustia ephimeropoides Tournier, 1889 (syn. of Picia sinuatocollis (Faust)) is designated as the type species of Faustia Tournier. Neotypes of Faustia caucasica Tournier, 1889 and Faustia millingi Tournier, 1889 and lectotypes of the following taxa are designated: Ephimeropus fenestratus Reitter, 1889, Ephimeropus flaveolus Reitter, 1889, Ephimeropus syriacus Reitter, 1889, Faustia ephimeropoides Tournier, 1889, Faustia mesopotamica Tournier, 1889, Hydronomus sinuatocollis Faust, 1885, Picia alfierii Pic, 1914, Picia distinctipennis Pic, 1901, Picia druinei Pic, 1917. On the basis of external characters, as well as the shape of the terminalia, Picia appears very closely related to the genus Echinocnemus Schoenherr, 1843.